Evaluation of sleep health of hospitalized children: A qualitative research from the perspective of children - Sümeyye Özarslan; Ulviye Günay; Didem Coşkun Şimşek (Adıyaman Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Aim: This study was conducted to determine sleep health of hospitalised children and the factors affecting sleep health. Material and Methods: This study was conducted with a qualitative descriptive design. It was carried out with 30 children aged between 9-15 years who were treated in the paediatric ward. The data were collected by one-on-one in-depth interview technique. Results: The study also found that the children experienced sleep problems. It has been found that environmental and emotional factors, as well as clinical routines and disease symptoms, have a significant impact on sleep efficiency. Furthermore, it has been observed that symptoms improve in some children, their sleep duration increases.Conclusion: The study results revealed that children experienced sleep problems during their hospital stay and were significantly affected by environmental and psychosocial factors related the hospital environment.